The Relationship between Internal Longitudinal Foot Arch with Static and Dynamic Balance of 12-14 years Male Students - seyed hamed musavi; behnam ghasemi; mohamad faramarzi (Sport Sciences and Health Research)
The purpose of this study was to investigate the relationship between internal longitudinal foot arch with static and dynamic balance in male students aged between 12 and 14. Statistical population of this research consisted of all guidance schools for boys in Shahrekord province and some were selected thorugh cluster sampling method. 90 subjects were randomly selected from these schools as the sample of this research. All subjects took the foot print test and their foot arch was quantatively classified by Staheli index. Then subjects with mean and standard deviation of age 13+0.82 years, weight 47+7.19 kg and height 1.54+0.086 cm were classified into three groups of 30 subjects. Then each group took one-leg standing balance test for static balance and star excursion balance test for dynamic balance. Results identified no significant relationship between foot arch and static balance but there was a significant relationship between foot arch and dynamic balance. Therefore, it seemed that there was a significant relationship between the quantity of internal longitudinal foot arch and dynamic performance of subjects and not only deep-sensitive receivers of foot sole but also the surface of foot sole play a role in controlling dynamic posture. Therefore, the results showed a relationship between the quantity of internal longitudinal foot arch and the control of body balance.